Smoking and Health: A Physician Responsibility—A Statement of the Joint Committee on Smoking and Health - Joint Committee on Smoking and Health (Canadian Respiratory Journal)
Tobacco use, particularly cigarette smoking, is a major cause of preventable disease and premature death worldwide. Both smokers and nonsmokers exposed to environmental tobacco smoke are at risk. Cessation of smoking reduces risks. Although the addicting properties of nicotine can make cessation difficult, both medical interventions aimed at helping smokers quit and social policies aimed at control of cigarette smoking can have significant benefits. Physicians should play an active role in control of smoking by ensuring that counselling and pharmacological therapy be available for the individual smoker. Physicians should also participate in the public debate regarding smoking both individually and through medical organizations. As smoking represents a threat to the public health, physicians must take a strong and active role seeking its control.